Analisis Wacana Kritis pada Pemberitaan TEMPO.CO tentang Kematian Taruna STIP JAKARTA - Maghvira, Genta (Jurnal The Messenger, 2017)
The purpose of this research is to know critical discourse analysis of the news about the death of taruna STIP that Tempo.co has been published. This research notice all of the aspects such as microstructure, meso-structure, and macrostructure. This research uses a news from Tempo.co with title Taruna STIP Tewas Dihajar Senior, Ini Kronologinya, online published in January 11th 2017. This research uses Norman Fairclough s critical discourse analysis model. Qualitative method has been used as basic thinking and critical paradigm as research standpoint. The result shows that Tempo.co does an election diction; use of the causation phrase; and selecting resource in direct quotation. Realization of the result rates in line with the Tempo.co s company mission. Which is to create an independent multimedia product that free from any pressure. There was a motivation in news produced which lead the reader to give a positive sight for Tempo.co.